The Miombo in transition: woodlands and welfare in Africa - Campbell, Bruce M. (Center for International Forestry Research, 1996)
Miombo woodlands are the most extensive vegetation type in Africa south of the equator. These dry tropical woodlands cover some 2.5 million hectares and are home to over 40 million people. Miombo products are very important to the livelihoods and basic needs of an additional 15 million urban Africans. The book demonstrates how much livelihood strategies of rural communities depend on miombo goods and services, and indicates the strong differentiation of uses within communities and in space and time. The ecological constraints to human activity in the region are clearly articulated, ranging from nutrient-poor soils to the presence of the tsetse fly. The authors also trace the host of policies that have influenced miombo woodlands and their uses, from pre-colonial times to the present. The current importance of miombo products in markets, both locally and globally, is documented in a chapter on trade patterns. Options for management are outlined, including silvicultural treatment, fire management and grazing regimes. Institutional arrangements, both local and state, for the management of the woodlands are investigated, and the authors examine how local communities can be empowered to manage and benefit from the woodlands. The final chapter proposes a conceptual model of how all the diverse social, economic, political and ecological processes interact to shape how the household and woodland situations are changing. This conceptual framework is then used to identify key issues for research, which will reduce gaps in current understanding and facilitate formulation of new management strategies, policies and institutions. The Miombo in Transition is a resource for researchers, with over 250 pages reviewing and synthesising over 400 studies. There are numerous figures, tables and plates. The book contains contributions by a number of researchers, and yet has managed to ensure coherence, close linking of chapters and complete coverage of material through authors' workshops and tight editorial control. Each chapter was reviewed by international experts both in draft and final format, resulting in the high quality of the final produc